2017
DOI: 10.3892/ol.2017.6910
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the presence of circulating tumor cells and the pathologic type and staging of non-small cell lung cancer during the early postoperative period

Abstract: This study investigated possible correlations between the presence of circulating tumor cells (CTCs) and the pathologic types and staging of non-small cell lung cancer (NSCLC) during the early postoperative period. Sixty-nine patients with NSCLC were enrolled in the study. Clinical staging was performed by postoperative pathological examination and imaging. Multiple mRNA in situ analyses targeting specifically expressed genes were carried out to identify the presence of CTCs. Correlations between age, sex, TNM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
3
11
1
Order By: Relevance
“…CTC clusters were found in 9/21 patients (Range 1–6 CTC clusters/mL; 1/4 Stage I, 2/4 Stage II, 2/8 Stage III, 4/5 Stage IV) (Figure 3A) where the size of CTC clusters ranged from 80.26 µm–353.10 µm (Figure 3B). Notably, single CTCs and CTC clusters (Figure 4A) were present at all stages of disease and the presence of CTC clusters increased with an advancement in staging, indicative of a higher burden of disease [32].…”
Section: Resultsmentioning
confidence: 99%
“…CTC clusters were found in 9/21 patients (Range 1–6 CTC clusters/mL; 1/4 Stage I, 2/4 Stage II, 2/8 Stage III, 4/5 Stage IV) (Figure 3A) where the size of CTC clusters ranged from 80.26 µm–353.10 µm (Figure 3B). Notably, single CTCs and CTC clusters (Figure 4A) were present at all stages of disease and the presence of CTC clusters increased with an advancement in staging, indicative of a higher burden of disease [32].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a study conducted by Xie et al have also indicated that the early diagnosis of metastasis and recurrence of lung cancer can be monitored via the changes of CTC before and after surgery or chemotherapy, which is helpful to improve the follow-up treatment regimen and thus enhance the survival rate. 27 Molecularly characterization of CTC is important to correlate gene mutation with tumor progression and to identify therapeutic targets for personalized therapies. A new research that assessed the degree of genomic similarity between pulmonary venous CTC (PV-CTC) in surgical resection, primary tumor and metastatic tumor has reported that CTC as a micrometastase is associated with tumor recurrence.…”
Section: Biofunction Of Gene Mutations In the Ctc Genomementioning
confidence: 99%
“…LUAD is often metastatic and has a relatively poor prognosis [4]. Chemotherapy, surgery, and radiotherapy are traditional treatments for LUAD [5,6], but the recurrence of early post-operative lung cancer patients are still very high [7]. Meanwhile, chemotherapy and targeted therapies have extensive drug resistance [8,9].…”
Section: Introductionmentioning
confidence: 99%